Optimization of adaptive and sustainable gold ore grinding processes for better environmental and land conditions in the small-scale gold mining sector in Indonesia - Nurjaman, Dadan Mohamad; Titah, Harmin Sulistiyaning; Kawigraha, Adji; Purwanti, Ipung Fitri; Hidayat, Wahyu (Journal of Degraded and Mining Lands Management, 2024)
The artisanal and small-scale gold mining (ASGM) sector largely relies on mercury in gold processing, posing potential environmental contamination, health issues, and land degradation. In the villages of Tatelu and Talawaan, ASGM operations, guided by local knowledge and resources, have transitioned to using cyanide leaching for gold processing sustainably. These operations utilize andesitic stones from river deposits as grinding media in the grinding process. However, the cyanide leaching results were not optimal, with a gold recovery below 60%. This leaves significant amounts of gold in the waste, necessitating further processing and the incomplete treatment of free cyanide waste. The suboptimal gold recovery in cyanide leaching is attributed to the inadequate grain size liberation during grinding. This study optimized grinding by comparing andesitic stone grinding media with steel balls and rods. The findings indicate that to achieve a grain size of 75% passing 74 um, grinding with andesitic stones takes 4 hours, while steel rods and balls take 3 hours. For a grain size of 75% passing 44 um, grinding with andesitic stones, steel balls, and rods requires 6 hours. With more precise process parameters, locally available andesitic stones can be an effective grinding medium to optimize gold recovery. In line with optimizing gold recovery, this will enhance ASGM's revenue, encouraging the adoption of waste management practices to alleviate environmental impact, health risks, and land degradation. This aligns with the promotion of sustainable practices within the ASGM sector.